Radixin inhibition decreases adult neural progenitor cell migration and proliferation in vitro and in vivo - Persson, Åsa; Lindberg, Olle R.; Kuhn, Hans Georg (Frontiers in Cellular Neuroscience, 2013)
Neuronal progenitors capable of long distance migration are produced throughout life in the subventricular zone (SVZ). Migration from the SVZ is carried out along a well-defined pathway called the rostral migratory stream (RMS). Our recent finding of the specific expression of the cytoskeleton linker protein radixin in neuroblasts suggests a functional role for radixin in RMS migration. The Ezrin-Radixin-Moesin (ERM) family of proteins is capable of regulating migration through interaction with the actin cytoskeleton and transmembrane proteins. The ERM proteins are differentially expressed in the RMS with radixin and moesin localized to neuroblasts, and ezrin expression confined to astrocytes of the glial tubes. Here, we inhibited radixin function using the quinocarmycin analog DX52-1 which resulted in reduced neuroblast migration in vitro, while glial migration remained unaltered. Furthermore, the morphology of neuroblasts was distorted resulting in a rounded shape with no or short PSA-NCAM positive processes. Intracerebroventricular infusion of the radixin inhibitor resulted in accumulation of neuroblasts in the anterior SVZ. Neuroblast chains were short and intermittently interrupted in the SVZ and considerably disorganized in the RMS. Moreover, we studied the proliferation activity in the RMS after radixin inhibition, since concentrated radixin expression has been demonstrated in the cleavage furrow of dividing cells, which indicates a role of radixin in cell division. Radixin inhibition decreased neuroblast proliferation, whereas the proliferation of other cells in the RMS was not affected. Our results demonstrate a significant role for radixin in neuroblast proliferation and migration.